Challenges of Treatment Decisions for Children With Hematological Malignancies Who Relapse After Hematopoietic Stem Cell Transplant: A Health Care Provider Perspective - Deborah Tomlinson; Sonia Lucchetta; Sarah Alexander; Sumit Gupta; Erilda Kapllani; Tal Schechter-Finkelstein; Jane Lowry; Joerg Krueger (Journal of Pediatric Hematology/Oncology Nursing, 2026)
Background When a child or adolescent's disease relapses following hematopoietic stem cell transplantation (HSCT), families are often presented with the complex decision to pursue further treatment with curative intent. This study aims to describe the experiences of health care professionals (HCPs) regarding choices after the first HSCT and factors influencing decision-making. Method This qualitative study included staff and trainee physicians, nurse practitioners, and nurse coordinators. All participants had experience caring for children who had received HSCT. Sampling was purposive. We applied a descriptive phenomenological study design using semistructured interviews. Interviews were recorded and transcribed. Two researchers analyzed and coded transcript data. Themes and subthemes were identified. Ranking and scoring of the importance of factors, using a visual analogue scale (VAS) ranging from 0 to 10, that could influence decision-making were examined. Results A total of 32 HCPs participated. We identified four themes: (a) navigating self; (b) factors affecting decisions; (c) child and family support; and (d) decision-making biases. There were 12 subthemes. When ranking importance in a list of nine factors, higher ranking was associated with chance of cure, child's quality of life, and the child's preference of treatment. Importance scoring for these three factors plus risks of severe short- and long-term health issues received the highest scores (VAS 9 or 10). Discussion Providing treatment with curative intent and involving the child in decision-making were important to HCPs. Chance of cure, child preference, quality of life, and risks of health issues were important factors. HCPs should consider the introduction of a palliative care team and discuss the chance of cure.